English Literacy Instruction for Chinese Speakers - Reynolds, Barry Lee.; Teng, Mark Feng.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Palgrave Macmillan, 2019)
Written with an emphasis on instruction, policy, practice, and assessment, this book focuses on English literacy at the pre-primary/primary, secondary, and university level, and discusses literacy policies in the region. An easy-to-read, solidly grounded book, it offers practical, thought provoking resources for classroom teachers and educators. It notably features explanations of key literacy skills, up-to-date research findings, and classroom applications that are contextualized for mainland China, Hong Kong, Macau, and Taiwan. This book provides pre-service and in-service teachers, English classroom practitioners, language teacher educators, literacy researchers, and students in research/teacher training programs a core set of instructional techniques on how to incorporate literacy-related ideas into English language classrooms. A valuable pedagogical resource for teaching and learning L2/EFL literacy, this book also highlights discussions on language and literacy policies and new examples of actual classroom teachers that have put English literacy instruction into practice.
INTRODUCTION -- English foreign and second language literacy development in Chinese Speaking Asia: What do we know? -- PART 1: ENGLISH LITERACY INSTRUCTION FOR PRE-PRIMARY AND PRIMARY EDUCATION -- Developing a school-based reading program for lower-grade primary learners: The case of a primary school in Hong Kong -- Measuring the vocabulary knowledge of Hong Kong primary school second language learners through word associations: Implications for reading literacy -- Second language literacy instruction for pre-primary learners in Hong Kong: Using stories, songs, and games -- The effectiveness of tailor-made content and language integrated learning materials for Taiwanese primary school students$1 (Bliteracy development -- English literacy instruction in Macau primary education: What can we learn from the Award Scheme on Instructional Design? -- PART II: ENGLISH LITERACY INSTRUCTION FOR SECONDARY EDUCATION -- English literacy development in Mainland Chinese secondary English classrooms: Pedagogical recommendations for enhancing formulaic language -- Spaced multi-draft composing and feedback in Mainland Chinese English as a foreign language secondary school writing literacy -- Evolution of writing assessment in Hong Kong secondary schools: Policy, practice, and implications for literacy development -- Developing thinking skills in English literacy instruction in Taiwanese secondary schools: Teachers$1 (Bperspectives -- Literacy skills education from the perspective of English as a Lingua Franca: A case study on Taiwanese students$1 (Bsecondary English language education experience -- Teaching reading in the Macau secondary English classroom: Some critical issues to consider -- PART III: ENGLISH LITERACY INSTRUCTION FOR TERTIARY EDUCATION -- Critical investigation of intercultural communication instruction: Building mainland Chinese university students$1 (Bcritical language awareness and intercultural literacy -- Innovating English literacy instruction: A writing center at a Chinese university -- Developing second language literacy: Taiwanese college students$1 (Berror types in focused feedback effectiveness -- Hong Kong college students$1 (Bperceptions of continuous assessment in the context of academic literacy instruction -- A longitudinal study of second language literacy instruction through assignment design at the university of Macau -- PART IV: EDUCATION POLICY TOWARDS ENGLISH LITERACY INSTRUCTION -- Language tug-of-war: When English literacy education encounters the national matriculation English test policy in mainland China -- The (3z(Bbiliterate and trilingual(3y (Bpolicy in Hong Kong primary school education -- Moving towards content-integrated English literacy instruction in Taiwan: Perspectives from stakeholders -- An examination of language planning and policy: Implications for language and literacy education in the Macau education system -- CONCLUSION -- English foreign and second language literacy instruction in Chinese speaking Asia: Future directions and implications.s
Keywords: Language and languages$1 (BStudy and teaching.s; Language policy; English language; Language Teaching; Language Policy and Planning; English